Five-Dimensional Chaotic System and its Circuitry Implementation - Jianliang Zhu; Hongchao Zhao (2009 2nd International Congress on Image and Signal Processing, 2009)
In order to generate complex chaotic attractors, a five-dimensional chaotic system is given,which has eleven parameters and consists of only a few amplifiers, multipliers, capacitors and resistors. These chaotic attractors obtained via computer simulation. To supplement the computer simulations physical circuit is designed. Numerical simulations and experimental circuit are given. The circuit of a new chaotic system realized is simulated using Multisin and the results were found to be identical to the numerical simulations of Matlab, which is important in practical applications in communication encryption etc.